DOI: 10.1007/978-3-540-68964-5_12
|View full text |Cite
|
Sign up to set email alerts
|

NO and sGC-Stimulating NO Donors

Abstract: Our knowledge of nitric oxide (NO) as a crucial endogenous signalling molecule continues to expand. Many, but not all, of the actions of NO are mediated by activation of soluble guanylyl cyclase (sGC) in target tissues. The aim of this chapter is to encapsulate the functions of NO in mammalian biology, tied to the chemistry of this unusual signalling entity. The experimental usefulness and therapeutic potential of the most widely utilised NO donor drugs is reviewed, with special consideration given to the impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…[51] 2. [52] Stimulation of sGC inhibits TGF-β-induced fibroblast activation with decreased expression and release of collagen. These inhibitory effects, however, are not dependent on the typical TGF-β downstream mediator SMAD3, but on reductions of TGF-β-mediated ERK phosphorylation and activation.…”
Section: Fgfr2-iiib (Bemarituzumab) Fgfr3 (Mfgr1877s) and Fgf23mentioning
confidence: 99%
See 1 more Smart Citation
“…[51] 2. [52] Stimulation of sGC inhibits TGF-β-induced fibroblast activation with decreased expression and release of collagen. These inhibitory effects, however, are not dependent on the typical TGF-β downstream mediator SMAD3, but on reductions of TGF-β-mediated ERK phosphorylation and activation.…”
Section: Fgfr2-iiib (Bemarituzumab) Fgfr3 (Mfgr1877s) and Fgf23mentioning
confidence: 99%
“…Upon binding of nitric oxide (NO), the soluble guanylate cyclase (sGC) catalyses the formation of cyclic guanosine monophosphate (cGMP) from guanosine‐5′‐triphosphate (GTP). Upon release from sGC, cGMP can act as a second messenger to activate further downstream targets, such as cGMP‐regulated ion channels, protein kinases (G‐kinases) and phosphodiesterases (PDEs), which regulate a variety of physiological processes, including cell growth and proliferation, vascular tone and remodelling, immune responses and neuronal transmission 52 …”
Section: Transforming Growth Factor β (Tgf‐β) Signalling—core Signallmentioning
confidence: 99%
“…Clinical application of NO or NO-donating drugs, however, is hampered by insufficient biometabolism, rapid development of tolerance and non-specific interactions of NO with other biological molecules. In particular, prolonged application or high concentrations of NO induce oxidative stress, cause DNA damage, prompt lipid peroxidation and alter protein function, which includes oxidation of the sGC rendering the enzyme unresponsive to NO 10 11. Since oxidative stress has been implicated in fibroblast activation, the toxic effects of NO may be particularly harmful in patients with SSc 1.…”
Section: Introductionmentioning
confidence: 99%
“…Implication of Cav2-Enzyme Assemblies for Cell Physiology. Our results indicate that upon coassembly with Cav2.2 channels both NOS1 and PKCβ can be reliably activated by short action-potential-like membrane depolarization, an alternative to activation of PKC by exogenously administered DAG derivatives or the use of NO donors for delivery of NO (30,31). In addition, these results showed that operation and properties of the two Cav2-enzyme assemblies closely resembled those of Cav2-BK Ca complexes (32).…”
Section: Discussionmentioning
confidence: 53%